A facile tandem double-dehydrative-double-Heck olefination strategy for pot-economic synthesis of (E)-distyrylbenzenes as multi-target-directed ligands against Alzheimer's disease employing C. elegans model. Issue 14 (5th April 2018) - Andhare, Nitin H.; Thopate, Yogesh; Shamsuzzama,; Kumar, Lalit; Sharma, Tanuj; Siddiqi, M.I.; Sinha, Arun K.; Nazir, Aamir
Abstract: A concise, one pot and regioselective access to (E) -distyrylbenzenes (DSBs) from arylhalide and secondary phenylenediethanol, a stable precursor for in situ generation of divinylbenzene (DVB) to avoid its polymerization, is described for construction of double CC bond formation via tandem double-dehydrative-double-Heck (D-D-D-H) reaction using Palladium and ionic liquid [hmim]Br as a cooperative catalyst. It is noteworthy that this pot-economy approach also provides direct synthesis of hydroxylated distyrylbenzenes without requirement of protection-deprotection strategy. Importantly, the synthesized DSBs are tested for their protective activity against β amyloid reduction, acetylcholine esterase inhibition, lipid lowering and reactive oxygen species (ROS) reduction properties in transgenic Caenorhabditis elegans model wherein 1, 3-bis(( E )-4-(trifluoromethyl)styryl)benzene (5c) is found to be active across all above factors thus presenting lead molecule within multi-target-directed ligands (MTDLs) approach. Molecular docking studies were also performed to understand the interactions of potent DSBs with receptors. Graphical abstract: